2010
DOI: 10.1523/jneurosci.5098-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Aggregates Cause Alterations of Astrocytic Metabolic Phenotype: Impact on Neuronal Viability

Abstract: Amyloid-␤(A␤)peptidesplayakeyroleinthepathogenesisofAlzheimer'sdiseaseandexertvarioustoxiceffectsonneurons;however,relatively littleisknownabouttheirinfluenceonglialcells.Astrocytesplayapivotalroleinbrainhomeostasis,contributingtotheregulationoflocalenergy metabolism and oxidative stress defense, two aspects of importance for neuronal viability and function. In the present study, we explored the effects of A␤ peptides on glucose metabolism in cultured astrocytes. Following A␤ 25-35 exposure, we observed an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
209
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(221 citation statements)
references
References 81 publications
7
209
0
1
Order By: Relevance
“…Similarly, we show that an ongoing A␤42 polymerization process, rather than distinct A␤42 aggregate states, also underlies previously reported alterations in astrocyte metabolic phenotypes (25). These findings contribute significantly to the understanding of amyloid formation and propagation in AD, provide novel insight into the mechanisms of A␤ protofibril toxicity, and carry important implications for designing anti-amyloid therapies.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Similarly, we show that an ongoing A␤42 polymerization process, rather than distinct A␤42 aggregate states, also underlies previously reported alterations in astrocyte metabolic phenotypes (25). These findings contribute significantly to the understanding of amyloid formation and propagation in AD, provide novel insight into the mechanisms of A␤ protofibril toxicity, and carry important implications for designing anti-amyloid therapies.…”
supporting
confidence: 77%
“…Crude A␤42 Preparations, but Not Monomers, Protofibrils, or Fibrils Alone, Increased Glucose Utilization by Cultured Astrocytes-We have previously reported that treatment of cultured astrocytes with A␤42, at comparable concentrations as used for cell viability measurements in the experiments described above, does not induce significant cell death but alters the astrocyte metabolic activity (25). We observed that A␤42 significantly enhances glucose utilization (uptake and phosphorylation), as assessed by 2-[ 3 H]DG uptake, by cultured astrocytes as compared with A␤40 (25).…”
Section: Separation Of Monomers From Protofibrils Retards A␤42 Fibrilmentioning
confidence: 95%
See 1 more Smart Citation
“…[193][194][195] In contrast, treatment with A␤ significantly increased glucose use in cultured astroglial cells by enhancing the activity of all major glucose metabolism pathways and glycogenesis. 196 Furthermore, co-culturing neurons with astrocytes pre-treated with A␤ significantly decreased neuronal survival as compared with co-culturing with naive astrocytes. 196 Analysis of the activity of metabolic enzymes similarly yielded controversial results: both decrease 197,198 and increase 195,199 in the activity of enzymes associated with glucose metabolism have been reported in AD brain preparations.…”
Section: Metabolic Remodeling Of Astroglia In Admentioning
confidence: 98%
“…196 Furthermore, co-culturing neurons with astrocytes pre-treated with A␤ significantly decreased neuronal survival as compared with co-culturing with naive astrocytes. 196 Analysis of the activity of metabolic enzymes similarly yielded controversial results: both decrease 197,198 and increase 195,199 in the activity of enzymes associated with glucose metabolism have been reported in AD brain preparations. These discrepancies may reflect opposite cell-specific changes in glucose metabolism developing at different stages of AD.…”
Section: Metabolic Remodeling Of Astroglia In Admentioning
confidence: 98%